Patterns in the Rain Rosas/Ictus: Steve Reich evening - Roy, Sanjoy (Dance Books Ltd., Alton,Hampshire (UK), 2008)
Rosas/Ictus: Steve Reich evening at Sadler's Wells. Since she began making dances in the early 1980s, Belgian Anne Teresa De Keersmaeker has swung between two poles. On one side are the expressionist, theatrical, multimedia pieces; on the other are Works that are deeply rooted in musical structures. That is apparent throughout De Keersmaeker's collaboration with the contemporary music ensemble Ictus, for a programme featuring the composer she has returned to most often: Steve Reich.